Aspek Keselamatan dan Kesihatan Pekerja Semasa Pandemik Covid-19 di Tapak Bina, Bandar Alor Setar, Kedah - Muhamad, Shahrul Addy Shazwan; Sarpin, Norliana; Omar, Roshartini; Masrom, Md. Asrul Nasid (Research in Management of Technology and Business, 2022)
The construction industry is one of the industries that has been affected due to the Covid-19 pandemic, especially related to the management of safety and health of workers at construction sites. Many initiatives have been introduced and implemented to curb worker safety and health issues, but there are still many positive cases occurring at construction sites. Therefore, the objective of this study is to identify critical aspects related to safety and health of workers at construction sites, identify methods of Covid-19 outbreak control methods to address safety and health issues of workers at construction sites and recommend measures taken by contractors to address safety issues. and the health of workers at construction sites during the Covid-19 pandemic. The scope of this study involves the management of a contractor company in the city of Alor Setar, Kedah. The methodology of this study is a qualitative method through interviews with 3 respondents from contractor organizations involved in construction site management. The findings of the study found that the main aspects of employee safety and health management during the Covid-19 pandemic are related to the effectiveness of SOP control in reducing the spread of Covid-19 pandemic. Meanwhile, the methods of controlling the spread of the epidemic used include the use of sanitation, the use of face masks and the care of the physical distance of workers on construction sites. In addition, measures to address safety and health issues at construction sites during the covid-19 pandemic are the implementation of the Movement Control Order (MCO) by the government, sanitation procedures at construction sites and the imposition of fines for non-compliance with SOPs. This study is expected to help the contractors in ensuring that an effective safety and health management system (SPKK) and standard operating procedures (SOP) at construction sites can be implemented and in turn can curb the spread of Covid-19 epidemic at construction sites in Malaysia.